Changes in land cover in coastal erosion hotspots in the southern Caribbean of Costa Rica during the period 2005-2017 - Sandoval-Murillo, Luis; Barrantes-Castillo, Gustavo (Uniciencia, 2021)
Studies conducted in recent years have warned us about the effects generated by changes in the coastline along the Southern Costa Rican Caribbean coast. The objective of this research is to evaluate this effect on land cover along the southern Costa Rican Caribbean coast. The methodology used consisted of surveying and comparing land cover from 2005 and 2016 (with field verification for 2017) along a 200 m wide coastal strip based on large-scale aerial photographs using ArcGis Map Algebra. In addition, covers affected by coastal erosion during the 2005-2010 and 2010-2016 periods are established by overlapping them with 2005 land covers, which helped identify the areas that changed from a beach to another type of use in the Cieneguita-Airport, Westfalia, Bananito, Cahuita-Puerto Vargas, Manzanillo, and Sixaola sectors. Results obtained indicate that, in the Cieneguita-Airport, Westfalia, Bananito, Manzanillo, and Sixaola segments, the main cover change was from beach to sea, with readjustments in other types of cover, while in Cahuita-Puerto Vargas the main change was from forest to ocean. In the Cieneguita-Airport segment, urban cover increased, which raises the risk of coastal erosion and public goods exposure. It is concluded that the effects of coastal erosion that occurred in critical points along the southern Caribbean have changed land cover. Beaches, grass, and coastal vegetation are the most affected since they are changed by sea surfaces, except for Cahuita National Park, where the ocean is eroding high- and low-density forests.